Proceedings of the 2018 International Conference on Quantitative InfraRed Thermography 2018
DOI: 10.21611/qirt.2018.p4
|View full text |Cite
|
Sign up to set email alerts
|

Teat traumatization in conventional and automatic milking system

Abstract: The aim of study was to evaluate teat traumatization caused by two milking system (CMSconventional milking system, AMSautomatic milking system). IRT method was used for the evaluation. The stables with AMS and CMS (tandem milking parlour) were included in the monitoring. The vacuum level was 42 kPa in both systems. Teat surface temperature was measured immediately before and after milking. The study showed that AMS had caused an insignificant increase of the teat temperature during milking compared to CMS. IRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…For instance, RGB cameras can identify changes in color and movement, however precision is lost when monitoring multiple animals at once, as each individual occupies fewer pixels in the video frame (Wu et al, 2023). Infrared thermography cameras have the ability to measure and image the heat radiation in the infrared part of the light spectrum emitted by any object, so it can offer insights regarding temperature deviations on an animal's body (Kunc et al, 2007). Finally, 3D cameras are able to reconstruct the animal's anatomy (totally or partially), which is useful to analyze anatomical asymmetries (Abdul Jabbar et al, 2017).…”
Section: Computer Vision Techniquesmentioning
confidence: 99%
“…For instance, RGB cameras can identify changes in color and movement, however precision is lost when monitoring multiple animals at once, as each individual occupies fewer pixels in the video frame (Wu et al, 2023). Infrared thermography cameras have the ability to measure and image the heat radiation in the infrared part of the light spectrum emitted by any object, so it can offer insights regarding temperature deviations on an animal's body (Kunc et al, 2007). Finally, 3D cameras are able to reconstruct the animal's anatomy (totally or partially), which is useful to analyze anatomical asymmetries (Abdul Jabbar et al, 2017).…”
Section: Computer Vision Techniquesmentioning
confidence: 99%
“…Using thermal imaging has led to significant results in detecting subclinical mastitis in dairy sheep and cows. Kunc et al [5] proposed IRT as a non-invasive tool for evaluating the milking process, including its potential for early mastitis detection in dairy cows. Colak et al [6] demonstrated a strong correlation between the udder skin surface temperature (USST) and the results of the California mastitis test (CMT) for 94 cows.…”
Section: Introductionmentioning
confidence: 99%